2014
DOI: 10.5812/numonthly.16385
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Malnutrition and Its Association With Biochemical Parameters in Patients With End Stage Renal Disease Undergoing Hemodialysis Using Subjective Global Assessment

Abstract: Background:Malnutrition is a common problem in patients with end stage renal disease (ESRD) undergoing hemodialysis that increases morbidity and mortality rate in them. Subjective global assessment (SGA) is a tool used by health care providers to assess nutritional status in these patients. In addition, biochemical parameters are used to assess the nutritional status in all people.Objectives:In this study, we evaluated the nutritional status of patients with ESRD undergoing hemodialysis using SGA and assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
6
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 19 publications
2
16
6
5
Order By: Relevance
“…60% of our elderly MHD patients had malnutrition (36.4% of patients had at mild-to-moderate and 23.6% of patients had at severe level) and MQSGA score was elevated with patients’ age. Even though, previous studies showed that malnutrition was significantly more frequent in women [12, 13], our study no significant correlation between malnutrition and gender. In elderly patients social isolation, cognitive dysfunction in maintaining basic nutritional requirements and depression may result in malnutrition.…”
Section: Discussioncontrasting
confidence: 93%
“…60% of our elderly MHD patients had malnutrition (36.4% of patients had at mild-to-moderate and 23.6% of patients had at severe level) and MQSGA score was elevated with patients’ age. Even though, previous studies showed that malnutrition was significantly more frequent in women [12, 13], our study no significant correlation between malnutrition and gender. In elderly patients social isolation, cognitive dysfunction in maintaining basic nutritional requirements and depression may result in malnutrition.…”
Section: Discussioncontrasting
confidence: 93%
“…28,29 A previous study by Jones et al 24 found significant differences in midarm circumference, midarm muscle circumference, and serum creatinine and CRP concentrations, but not serum albumin concentrations, between patients classified as SGA A (WN) and B (mildly to moderately MN). In addition, they showed that the composite nutrition score was associated with the 3-point SGA score, 7-point SGA score, BMI, midarm circumference, and triceps skinfold, except for serum albumin concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…For these reasons, SGA is recommended by European Renal Best Practice as a good tool to screen nutritional status in the elderly [10]. However, SGA still can be criticized for its subjectivity, and thus potential problems for reproducibility [28,29], and several authors report different results on the association of SGA with more objective nutritional markers [30,31]. Further SGA takes some time and expertise to be evaluated, making it less suitable in fact for routine use as a regular screening tool in a busy dialysis unit.…”
Section: Plos Onementioning
confidence: 99%